1999
DOI: 10.1246/bcsj.72.2719
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopy, Electrochemistry, and Mesomorphism of Triple-Decker Porphyrins Consisting of Two Cerium Ions and Three 5,15-Diarylporphyrins

Abstract: Triple-decker sandwich complexes, which consist of two cerium ions and three strip-like diarylporphyrins, have been synthesized and their spectroscopic and electrochemical properties and mesomorphism are reported and compared with those of the corresponding double deckers and the parent monomers. The Soret band of the triple-deckers lies at longer and shorter wavelengths than those of the double-deckers and monomers, respectively, while a sequence of small absorptions is observed in the Q band region. These ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 16 publications
3
35
0
Order By: Relevance
“…Synthesis, characterization, and properties of the ligand L11 and of its lanthanide complexes 3 ] 2 in the solid state: As previously discussed in the introduction, the increasing number of divergent flexible alkyl chains in the polycatenar ligand in going from L9 (n = 2) to L10 (n = 6) significantly reduces the melting temperature by DT m = 119 8C, a phenomenon tentatively assigned to a large and enthalpically unbalanced increase of DS m . [10] To further exploit this effect, six additional peripheral dodecyloxy chains have been connected to the central tridentate 2,6-bis-(benzimidazol-2-yl)pyridine binding unit in the target ligand L11.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Synthesis, characterization, and properties of the ligand L11 and of its lanthanide complexes 3 ] 2 in the solid state: As previously discussed in the introduction, the increasing number of divergent flexible alkyl chains in the polycatenar ligand in going from L9 (n = 2) to L10 (n = 6) significantly reduces the melting temperature by DT m = 119 8C, a phenomenon tentatively assigned to a large and enthalpically unbalanced increase of DS m . [10] To further exploit this effect, six additional peripheral dodecyloxy chains have been connected to the central tridentate 2,6-bis-(benzimidazol-2-yl)pyridine binding unit in the target ligand L11.…”
Section: Resultsmentioning
confidence: 96%
“…[1] Pioneering research efforts indeed focussed on two well-identified classes of complexes that incorporated trivalent lanthanides, Ln III , and exhibited thermotropic liquid crystalline properties. 1) Neutral disk-like sandwich complexes [LnA C H T U N G T R E N N U N G (Li-2H) 2 ] (i = 1-5, as shown) [2] or triple-decker complexes [Ce 2 (Porphyrin) 3 ] [3] have been shown to stack on top of each other to produce hexagonal columnar mesophases (Col h ) in the 20-250 8C range, whereas; 2) lanthanide size-dependent lamellar organizations (usually smectic A, SmA) have been established to be common for the rod-like complexes [LnA C H T U N G T R E N N U N G (Li-H) 3 X 3 ] (i = 6-8; X = NO 3 , H 25 C 12 OSO 3 , Cl, b-diketonate).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations